Formative assessment in university context: opportunities and proposals for action - Cañadas, Laura (2020)
Assessment is one of the most important and controversial elements of University training. Despite the extensive bibliography that supports the use of formative assessment processes in Higher Education, in practice, there is still a great predominance in the use of traditional assessment systems that seek to stablish a grade at the end of the training period. The aim of this article is to carry out a review of the concepts of assessment and show the characteristics that formative assessment processes in Higher Education must have, in order to make a series of recommendations and proposals that can serve as reference elements for the change in the assessment processes. It is necessary to advance in the use of these procedures in a systematic and planned way to achieve a more formative environment in a system that keeps a single numeric grade as the culmination of the process.